Peran Pemerintah dalam Pengembangan Pertanian Berkelanjutan (Studi tentang Pengembangan Padi Organik di Pemerintah Kabupaten Sragen) - Hariyoko, Yusuf (Jurnal Administrasi Publik, 2013)
Abstract : The Role of Government in the Sustainable Agriculture Development (A Study of the Development of Organic Rice in the Government of Sragen). The role of government in development is an absolute must, is also the development of sustainable agriculture. Implementation of sustainable agriculture in Sragen itself is inseparable from the role of local government through the relevant agencies of the concept development. The relevant agencies have different roles related and complementary. Factors supporting the role of government in agricultural development is institutional, public awareness, availability of land, technology development, and the role of the private sector. While the inhibiting factor is land use, limited human resource capacity, infrastructure equity, availability and use of technology, and chemical drugs that are not environmentally friendly. The advice given is to provide assistance to the contributing factors in order to function optimally, developing regions in high-potential areas, and to improve the quality of human resources ( farmers and PPL ) and improve the distribution of agricultural inputs. Keywords : the role of government, sustainable agricultureAbstrak: Peran Pemerintah dalam Pengembangan Pertanian Berkelanjutan (Studi tentang Pengembangan Padi Organik di Pemerintah Kabupaten Sragen). Peran pemerintah dalam pembangunan merupakan hal yang mutlak, tidak terlepas juga pengembangan pertanian berkelanjutan. Penerapan pertanian berkelanjutan di Kabupaten Sragen sendiriÂ  tidak terlepas dari peran pemerintah daerah melalui instansi terkait pengembangan konsep tersebut. Instansi terkait tersebut memiliki peran berbeda yang terkait dan saling melengkapi. Faktor pendukung peran pemerintah dalam pengembangan pertanian tersebut adalah kelembagaan, kesadaran masyarakat, ketersediaan lahan, pengembangan teknologi, dan peran swasta. Sedangkan yang menjadi faktor penghambatnya adalah alih fungsi lahan, keterbatasan kemampuan SDM, pemerataan sarana prasarana, ketersediaan dan pemanfaatan teknologi, dan obat kimia yang tidak ramah lingkungan. Saran yang diberikan adalah dengan memberikan bantuan pada faktor pendukung agar dapat berfungsi lebih optimal, mengembangkan wilayah di daerah yang berpotensi tinggi, serta meningkatkan kualitas SDM (petani dan PPL) dan meningkatkan pemerataan sarana pertanian.Kata kunci: peran pemerintah, pertanian berkelanjutan